Modifying the Rizzoli foot model to improve the diagnosis of pes‐planus: application to kinematics of feet in teenagers - Nicola Portinaro; Alberto Leardini; Artemisia Panou; Valerio Monzani; Paolo Caravaggi (Journal of Foot and Ankle Research, 2014)
Abstract Background A number of multi‐segment foot protocols have been proposed to obtain measurements of clinical value. In the clinical assessment of foot pathologies and deformities, such as in the pes‐planus, the frontal‐plane alignment of the calcaneus and the dynamic properties of the medial longitudinal arch are critical parameters though often neglected by the majority of foot protocols. The aim of the present work is to modify an established foot protocol to obtain static and kinematic measures more consistent with corresponding clinical observations. Moreover, while many papers have reported kinematic data from varying populations, few investigations have focussed on young participants from same‐age cohorts. Methods A 6‐camera motion capture system was employed to track the shank, rear‐, mid‐ and fore‐foot segments in the left and right leg of 10 children (13.1 ± 0.8 years) during gait. Three markers were attached to each segment thus allowing for triplanar motion of five joints to be described according to the Rizzoli Foot Model. An additional marker was attached to the posterior bottom of the calcaneus to enhance measurement of frontal‐plane orientation. Description of the medial longitudinal arch angle was redefined to be more consistent with rearfoot orientation and to common clinical assessments. A novel 3‐marker description of the hallux segment was implemented to improve robustness in calculating 1st metatarso‐phalangeal joint rotations. Results Foot segments kinematics showed good inter‐ participant repeatability and overall consistency with previous similar reports. 15 out of 20 feet showed neutral or slightly valgus orientation of the calcaneus. Relatively large medial longitudinal arch angles (mean 186 ± 16 deg) were found in the present young population. Both measurements were reasonably in accordance with the relevant clinical observations of these feet. Conclusions Modifications to a widely used multisegmental foot kinematic model were implemented to improve robustness and consistency with relevant clinical observations. A detailed description of foot joints motion during barefoot walking in a population of 13‐year old children with apparent flat feet has been presented, which may provide useful information to investigate the development of gait in children and the diagnosis of flexible flat foot.